Can High-Speed Rail Help Achieve Urban Green Development? From a Spatial Perspective - Liu, Shuai; Zhang, Yumeng; Cao, Jianhua (Frontiers in Environmental Science, 2022)
As a convenient means of transportation, high-speed rail (HSR) plays an important role in green development. In the context of the rapid development of China’s HSR, this paper selects the SBM-DDF-SML model to construct the green total factor productivity (GTFP) index to measure urban green development; moreover, it empirically tests the impact of the opening of HSR on GTFP using the spatial difference-in-differences (SDID) model. The results show that the opening of HSR could significantly promote GTFP for HSR-served cities. In addition, the opening of HSR has a positive effect on the GTFP for neighboring HSR-served cities but a negative impact on that for neighboring non-HSR-served cities. The mechanism test shows that HSR can influence GTFP by promoting urban green innovation and entrepreneurial vitality. This study is a supplement to the research on the impact of HSR on the GTFP, in order to provide corresponding policy advice. The government should optimize the layout of HSR and help cities to achieve green and sustainable development.